Screening of cytotoxic activities toward WiDr and Vero cell lines of ethyl acetate extracts of fungi-derived from the marine sponge Acanthostrongylophora ingens - Ibtisamatul Aminah, Andani Eka Putra, Dayar Arbain, Dian Handayani (Journal of Applied Pharmaceutical Science, 2019)
Ethyl acetate extracts of fungi-derived from the marine sponge Acanthostrongylophora ingens were tested for cytotoxic activity against WiDr and Vero cell lines. Three of fungi extracts exhibited strong cytotoxicity with percentage of viability (≤50%) occurring at concentrations of 100 μg/ml. One isolate (IB141) showed specific cytotoxicity against WiDr cells whreas not against Vero cells. This isolate was identified based on molecular characterization using sequence analysis of the partial 18S rRNA gene. The result indicated that IB141 was identical to Aspergillus ochraceus. A comparatively high part of positive bio-activity screening results were acquired in this study, displaying that the fungi-derived from the marine sponge A. ingens have potential as a source of new anti-cancer agents.
Keywords: Acanthostrongylphora ingens, Aspergillus ochraceus, cytotoxic activity, marine sponge derived fungi, molecular identification.